A research model to study research-practice partnerships in education. Issue 1 (8th December 2020) - Cooper, Amanda; MacGregor, Stephen; Shewchuk, Samantha
Abstract : Purpose: This scoping review utilizes findings from 80 articles to build a research model to study research-practice-policy networks in K-12 education systems. The purpose of this study was to generate a broad understanding of the variation in conceptualizations of research-practice-policy partnerships, rather than dominant conceptualizations. Design/methodology/approach: Arskey and O'Malley's (2005) five stage scoping review process was utilized including: (1) a consultative process with partners to identify research questions, (2) identify relevant studies, (3) study selection based on double-blind peer review, (4) charting the data and (5) collating, summarizing and reporting the results in a research model identifying key dimensions and components of research-practice partnerships (RPPs). Findings: Coburn et al. (2013) definition of RPPs arose as an anchoring definition within the emerging field. This article proposes a model for understanding the organization and work of RPPs arising from the review. At the core lies shared goals, coproduction and multistakeholder collaboration organized around three dimensions: (1) Systems and structures: funding, governance, strategic roles, policy environment, system alignment; (2) Collaborative processes: improvement planning and data use, communication, trusting relationships, brokering activities, capacity building; (3) Continuous Learning Cycles: social innovation, implementation, evaluation and adaptation. Research limitations/implications: By using a common framework, data across RPPs and from different studies can be compared. Research foci might test links between elements such as capacity building and impacts, or test links between systems and structures and how those elements influence collaborative processes and the impact of the RPPs. Research could test the generalizability of the framework across contexts. Through the application and use of the research model, various elements might be refuted, confirmed or refined. More work is needed to use this framework to study RPPs, and to develop accompanying data collection methods and instruments for each dimension and element. Practical implications: The practical applications of the framework are to be used by RPPs as a learning framework for strategic planning, iterative learning cycles and evaluation. Many of the elements of the framework could be used to check-in with partners on how things are going – such as exploring how communication is working and whether these structures move beyond merely updates and reporting toward joint problem-solving. The framework could also be used prior to setting up an RPP as an organizing approach to making decisions about how that RPP might best operate. Originality/value: Despite increased attention on multistakeholder networks in education, the conceptual understanding is still limited. This article analyzed theoretical and empirical work to build a systematic model to study RPPs in education. This research model can be used to: identify RPP configurations, analyze the impact of RPPs, and to compare similarities and differences across configurations.